2001
DOI: 10.1136/heart.85.4.390
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differentials in recurrent ischaemia and mortality after acute myocardial infarction

Abstract: Objective-To examine the influence of socioeconomic deprivation on case fatality following acute myocardial infarction. Design-Prospective cohort observational study. Setting-General hospital. Patients-1417 white and south Asian patients admitted with acute myocardial infarction between January 1988 and December 1996, and classified by the Carstairs socioeconomic deprivation score of the enumeration district of residence. Main outcome measures-30 day and one year survival. Results-There was little variation ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 19 publications
1
46
1
Order By: Relevance
“…[2][3][4] By contrast, very little inequality was apparent in small cohorts from the United Kingdom, Italy, and France. 5,29,30 The disparity highlights the health benefits of universal healthcare.…”
Section: Socioeconomic Inequalitymentioning
confidence: 99%
“…[2][3][4] By contrast, very little inequality was apparent in small cohorts from the United Kingdom, Italy, and France. 5,29,30 The disparity highlights the health benefits of universal healthcare.…”
Section: Socioeconomic Inequalitymentioning
confidence: 99%
“…[6][7][8] However, a recent Canadian study found no significant association between SES and mortality up to one year after hospitalisation. 9 In Europe, fatality rates in the first month were significantly higher among less privileged patients in Finland 3 and England, 10 but not Scotland 1 ; increased mortality in the first year was associated with low SES in Finland, 3 but not England. 10 Results on inequities in non-invasive treatments for cardiovascular disease are inconsistent.…”
mentioning
confidence: 95%
“…9 In Europe, fatality rates in the first month were significantly higher among less privileged patients in Finland 3 and England, 10 but not Scotland 1 ; increased mortality in the first year was associated with low SES in Finland, 3 but not England. 10 Results on inequities in non-invasive treatments for cardiovascular disease are inconsistent. [9][10][11][12] In many locations, underprivileged groups are less likely to receive invasive and diagnostic procedures and more likely to experience delays in these types of care.…”
mentioning
confidence: 95%
“…[1][2][3][4] For example, compared to other patients, socially disadvantaged patients have a higher incidence of cardiovascular disease [4][5][6][7] and a poorer prognosis once cardiovascular disease has become clinically apparent. [8][9][10][11] Social scientists use the term socioeconomic gradients for associations between disease and socioeconomic status. In explaining these gradients, it is important to identify the contributions of risk factors for disease and to distinguish them from the contributions of poor access to health services, both preventive and therapeutic.…”
mentioning
confidence: 99%